ENDOTHELIN-1 IN PATIENTS WITH ISCHEMIC HEART DISEASE ("Conference on Universal Science Research 2023", 2024)
Ishemia or ischemic heart disease is the leading cause of disability and premature deaths worldwide. IHD is a condition in which the heartis starved of oxygen due to a redused blood spply. Deapite a large pool of interesting candidate biomarkers, endothelin-1 (ET-1) appears to be involvedin multiple aspecis of IHD pathogenesis that include neurohormonal activation, cardiac remodeling, endothelial dysfunction, inflammation, atherosclerosis and alteration of the renal function. ET-1 production and release can be upregulated by inflammatory factors, such as IFN-γ and IL-1β, during disease